Is Our City Livable and Healthy in the Post-SARS Era? Re-designing Healthy Cities – a Lesson from Hong Kong - S. S. Y., Lau (Journal of Architectural/Planning Research and Studies (JARS), 2018)
The paper draws an attention on the academic debate on the pros and cons of compact city, one that embraces a high-density and high-rise, mixed land-use urban form. The paper supports compact city as a candidate for sustainable urban form by reviewing and discussing recent new initiatives from Hong Kong in the post-SARS era that includes research and development efforts by academia and governments on the evaluation and derivation of guidelines for design implementation and building management operations at the urban design and building design levels. Similarly, innovative initiatives are also found in the collective efforts by statutory bodies, developers and professionals to improve the standard and quality of the habitable environment. The discussion is based on selected case studies from recently realized projects in the residential market; as well as applied research programs undertaken by universities and government. The summary is that recent efforts in Hong Kong show that there is confidence for a high density compact city to be a livable and healthy city. In the paper, the reference to ‘health,’ ‘hygiene’ or ‘healthy buildings’ is a causal usage. The three terms project a layperson’s perception of the quality of the physical environment. In this way, the terms have no specific medical connections.